Anxiety disorders, post-traumatic stress disorder, and obsessive–compulsive disorder. (November 2016) - Gordon, Robert P.; Brandish, Emma K.; Baldwin, David S.
Abstract: Anxiety symptoms and disorders are common in community settings and primary and secondary care. Symptoms can be mild and transient, but many people are troubled by severe symptoms causing great personal distress and impairing social and occupational function. The societal burden from anxiety disorders is considerable, but many who might benefit from treatment are not recognized or treated by healthcare professionals. Some patients, however, are given unnecessary or inappropriate treatment. Recognition relies on keen awareness of the psychological and physical symptoms of all anxiety disorders, and accurate diagnosis on identification of the specific features of particular disorders. Need for treatment is determined by the severity and persistence of symptoms, level of associated disability and impact on everyday life, presence of coexisting depressive symptoms, and other features such as good response to or poor tolerability of previous treatments. Choice of treatment is influenced by patient characteristics, patient and doctor preferences, and local availability of potential interventions. There is much overlap between different anxiety disorders in evidence-based and effective therapies (e.g. prescription of a selective serotonin reuptake inhibitor or course of individual cognitive behavioural therapy), but there are important differences. It thus helps to become familiar with the characteristic features and evidence base for each disorder.